Exploring the health benefits of traditionally fermented wax gourd: flavor substances, probiotics, and impact on gut microbiota - Nannan Wang; Wei Bao; Moussa Gouife; Jiajie Xu; Jiaojiao Han; Chengyang Lu; Chengyang Lu; Tinghong Ming; Jun Zhou; Jun Zhou; Wenwen Zhang; Xiurong Su; et al. (Frontiers in Sustainable Food Systems, 2024)
BackgroundThe fermented wax gourd, often referred to as “smelly wax gourd,” is a traditional food that undergoes natural fermentation. It’s a staple in eastern China and is recognized as Ningbo’s “city-fermented food.” Characterized by its distinct putrid flavor and soft texture, its safety, nutritional aspects, and sensory attributes have not been extensively studied.MethodsIn this research, the microbial community and flavor components of fermented wax gourd during its traditional fermentation were analyzed. The safety and impact on the gut microbiota were also assessed by administering it to healthy and pseudo-germ-free mice.ResultsThe findings revealed that organic acids primarily contribute to the gourd’s flavor during fermentation. The aroma reminiscent of fruits is due to 2-methyl-butyric acid, while butyric, pentanoic, caproic, and octanoic acids are responsible for their characteristic smelly taste. In the fermentation of traditional foods, the abundance of substances and open fermentation contribute to the diversity of microorganisms in the system, and the reproduction and metabolism of microorganisms drive the fermentation of foods. From the results of this study, the flavor peaks on the 10th day of fermentation. Predominant microbes include Lactobacillus fermentum, Streptococcus equinus, Fusobacterium perfoetens, Weissella confusa, and Lactobacillus plantarum. Notably, Lactobacillus was the most abundant probiotic in the early fermentation stages. The “smelly” taste of smelly wax gourd was mainly derived from butyric acid, valeric acid, caproic acid, caprylic acid, p-methylphenol and other compounds, and the abundance of Caldicoprobacter algeriensis, Mariniphaga anaerophila, Streptococcus equi and Lactobacillus were significantly correlated with 4 of the above 5 acids. These four bacteria may contribute more to the “smelly” taste of smelly wax gourd. In the study, compared with the control group (CONT), the abundance of Helicobacter ganmani, H. Chanicola, Lactobacillus animalis, Lactobacillus gadi and Lactobacillus reuteri decreased in mice groups treated with anti-biological pretreatment followed by gavage of smelly wax gourd (A.SWG) and the smelly wax gourd (SWG) groups. Conversely, Muribaculum intestinale, Prevotellamassilia timonensis, Alistipes putredinis, Kineothrix alysoides and Clostridium indolis’ abundance of increases. Mice that underwent fecal microbiota transplantation (FMT) exhibited a higher abundance of probiotics like Bifidobacterium animalis, Bifidobacterium pseudolongum, Lactobacillus johnsonii, and others compared to the fecal culture microbiota transplantation (CMT) group. However, the CMT group had a higher presence of fermented and Royce lactobacilli.ImplicationConsuming fermented wax gourd can enhance the presence of beneficial probiotics and reduce pathogenic Helicobacter sp. in the mouse gut. Both Lactobacillus sp. and Bifidobacterium sp. showed increased abundance post fecal microbiota and fecal culture microbiota transplantation.